From the Crisis of Questioning: Considerations About Practices and Reflections on Graduation Projects - Dobles-Trejos, Cecilia (2020)
This article is based on the experience of some male and female academics from the Basic Education Division, Center for Research and Teaching in Education of Universidad Nacional (the Graduation Project Faculty Committee). It offers a conversational approach aimed at promoting personal growth for both researchers and faculty members. It does so based on a retrospective view of university training of educators, with support from research in that field, in a critical, reflexive way, and involving their capacity for astonishment. Besides, it considers the challenges posed by pedagogical tasks based on the research question as a way to make discoveries about their teaching practices. This research focus on university formation with meaning and purpose (Mora Alvarado and Gómez Torres, 2017) starts from a reflection on questions as a basis for a dialogical relationship in the pedagogical practice and is the theoretical support for this essay. Research is seen as a process, leaving behind the traditional view that a research proposal starts from a “blueprint.” Instead, it unites students and tutors, working together to bring about knowledge to grow both personally and professionally. In other words, it is not about thinking of graduation projects as ends in and of themselves, but rather as a way to provide students with tools to expand research skills as a means to recover their capacity for astonishment, and especially to acknowledge their ability to create new knowledge.